1970
DOI: 10.3329/jom.v8i2.1404
|View full text |Cite
|
Sign up to set email alerts
|

Views of the Students and Teachers about the New Curriculum (Curriculum 2002) and Their Opinion on in-Course Assessment System

Abstract: Background: The academic activities of the 1st and 2nd year MBBS students are running according to the new curriculum (Curriculum 2002). Curriculum is a series of planned activities to which the learner may be exposed in order to achieve the learning goals. But due to ongoing modifications of society, disease demography, medical science, concepts of teaching and availability of newer technique; curriculum may need to be changed. Assessment is the process of testing a student's ability. A good assessment should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Our students also favoured regular assessment tests but they suggested that internal assessment exams should not be too frequent. This observation is in accordance with other studies that suggest assessment as an essential part of teaching learning process but very frequent assessments reduce the time for selfpreparation by the students (Ahmed et al, 2007).…”
Section: Details Of Optionssupporting
confidence: 93%
See 1 more Smart Citation
“…Our students also favoured regular assessment tests but they suggested that internal assessment exams should not be too frequent. This observation is in accordance with other studies that suggest assessment as an essential part of teaching learning process but very frequent assessments reduce the time for selfpreparation by the students (Ahmed et al, 2007).…”
Section: Details Of Optionssupporting
confidence: 93%
“…It should be recognized that present day the medical students cannot be expected to learn as much physiology as was the case in the past but it should also be recognized that knowledge of physiology as a core discipline is fundamental to health and disease (Ahmed et al, 2007). Our study reveals that students are interested in learning the subject from a clinical application.…”
Section: Resultsmentioning
confidence: 72%
“…Skills assessment does not only measure the performance but also provides an indication of the effectiveness of learning strategies and appropriateness of the content input. A good assessment should be valid, reliable, practicable, and should have educational value (Ahmed et al 2007).…”
Section: Practice Pointsmentioning
confidence: 99%
“…As medical curricula around the world move from discipline-based to integrated teaching and learning, the integration of assessment must necessarily follow (Hudson & Tonkin 2004). A change in instructional methods without changing assessment will not achieve desired outcomes (Ahmed et al 2007). Studies have shown that such a mismatch can eventually lead to failure of any adopted curriculum (Ghosh & Pandya 2008).…”
Section: Introductionmentioning
confidence: 99%